RESEARCH OF PROPERTIES AND CHEMISM OF DOUBLE SUPERPHOSPHATE (Academicia Globe: Inderscience Research, 2021)
Over the past decade, the chemical industry has undergone dramatic changes: new technologies are being introduced in practice and development has begun. These changes have led to a higher level of technological processes and devices in production. Technologies for the production of double superphosphate began to develop rapidly. Research work is aimed at improving the quality of the product, that is, its physical and chemical properties.